2011
DOI: 10.1259/bjr/53865832
|View full text |Cite
|
Sign up to set email alerts
|

Organ and effective dose reduction in adult chest CT using abdominal lead shielding

Abstract: Objectives: The purpose of this study was to evaluate and compare organ and effective dose savings that could be achieved using conventional lead aprons and a new, custom-designed shield as out-of-plane shielding devices during chest CT scans. Methods: Thermoluminescent dosimeters were used to measure doses throughout the abdomen and pelvis during CT scans of the chest of a RANDO phantom. Dose measurements were made with no shielding, with lead aprons and with the new shield around the abdomen and pelvis in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…There was a measurable (absolute) dose reduction in regions within the phantom, outside the primary beam, with the use of the abdominal shield (Figure 2), which was greatest near the edge of the X-ray field and closer to the surface. In relative terms, however, the dose reduction increases as the distance from the primary beam edge increases and the depth in the phantom decreases ( Figure 3)-which is in agreement with the results of a previous phantom study that investigated the effectiveness of an abdominal shield used during chest CT. 9 The dose reduction to the phantom voxels protected with the shield was very small and did not exceed 0.09 mGy for voxels at 4 cm or deeper from the phantom surface. In a voxel at a depth of 8 cm and at 15 cm from X-ray field (corresponding approximately to the level of the uterus and ovaries), the dose reduction was about 0.035 mGy or approximately 4% of the dose value in that voxel when the abdominal shield was not used (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…There was a measurable (absolute) dose reduction in regions within the phantom, outside the primary beam, with the use of the abdominal shield (Figure 2), which was greatest near the edge of the X-ray field and closer to the surface. In relative terms, however, the dose reduction increases as the distance from the primary beam edge increases and the depth in the phantom decreases ( Figure 3)-which is in agreement with the results of a previous phantom study that investigated the effectiveness of an abdominal shield used during chest CT. 9 The dose reduction to the phantom voxels protected with the shield was very small and did not exceed 0.09 mGy for voxels at 4 cm or deeper from the phantom surface. In a voxel at a depth of 8 cm and at 15 cm from X-ray field (corresponding approximately to the level of the uterus and ovaries), the dose reduction was about 0.035 mGy or approximately 4% of the dose value in that voxel when the abdominal shield was not used (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 90%
“…5,6 A similar practice, often referred to as "out-of-plane" shielding, has also found an application in dental radiography and CT, where there were reports of a noticeable dose reduction to shielded organs. [7][8][9] During chest X-ray examinations, the use of abdominal shields complicates and possibly compromises the procedure, and their role in reducing patient dose is controversial. While Njeh et al 6 found a negligible radiation protection effect from the use of abdominal shields during chest X-ray examinations, Hashimoto et al 10 and Jackson et al 11 reported a significant level of dose reduction.…”
Section: Introductionmentioning
confidence: 99%
“…We found 11 relevant articles, listed in Table 1 [3,[11][12][13][14][15][16][17][18][19][20]. All of them reported uterus exposure due to CT imaging performed for exclusion of pulmonary embolism (PE).…”
Section: Literature Reviewmentioning
confidence: 99%
“…30 % (Reduktion der Organdosis um 23 μSv) [7,18]. Eine vergleichbare Reduktion der anderen Bauchorgane (z.…”
Section: Ct Des Thoraxunclassified